Reference to the realm of nature in the theoretical reflections and the music of Ludomir Michał Rogowski - Wójtowicz, Ewa (Interdisciplinary Studies in Musicology, 2018)
Besides an abundant musical output, the rich legacy of Ludomir Michał Rogowski (1881-1954) also contains numerous writings, a special place among which is held by Muzyka przyszłości [The music of the future], written in 1919 and published three years later. In this work Rogowski asserted that the possibilities for composing music on the basis of the major, minor and chromatic scales were exhausted. He went on to propose an expansion of the repertoire of scales, giving two criteria for the choice of scales: ‘naturalness’ and ‘rhythmicity’. A ‘natural’ scale is one which can be read from the sequence of fifth steps of the twelve-note chromatic scale in equal temperament. The simplest example is the anhemitonic pentatonic scale. The concept of the renewal of tonal material is central to Muzyka przyszłości, but its author formulates an idea about the rhythmic essence of musical form as well. In his considerations on this subject, he proceeds from the nature-related phenomenon of symmetry. He treats the simplest symmetrical pattern, the ternary form ABA, as an elementary manifestation of rhythm expanded into form. References to nature also occur in Rogowski’s texts on national music. In this context, folk music represents such values connected with nature as simplicity, honesty and freshness; it is devoid of all artificiality or posture, free from all convention. In Rogowski’s musical output, a fascination with nature became a powerful source of inspiration, from which many symphonic works of a programmatic character emerged. The connection with nature and joy of life - the crucial values of Mediterranean culture - are conveyed by the music of Cortege de Dionysos and by the whole of composer’s oeuvre. Rogowski confirmed his belonging to the culture of the South not only with his music. When, in 1926, he left Warsaw for Dubrovnik, he confirmed it also with his life.